Adolescent and Young Women’s Daily Reports of Emotional Context and Episodes of Dating Violence - Matson, P. A. (Journal of family violence, 2021)
To investigate same day, previous day, and next day associations between trust, closeness, commitment, jealousy and provision of instrumental support with dating violence victimization and perpetration. A convenience sample of young women, 16–19 years, in a heterosexual dating relationship with at least one act (past month) of physical or psychological victimization or perpetration, were recruited from urban public locations. Participants answered questions daily via text continuously for four months on dating violence and partner-specific emotions. Daily surveys asked about trust, closeness, commitment for their partner, jealousy, perceptions of partner’s jealousy and provision of instrumental support to and from partner, and dating violence victimization and perpetration. Multilevel modeling examined within-relationship associations over time. Mean (sd) age for the full sample was 18.1 (1.1) years. Same-day emotional context (trust, closeness, commitment, jealousy and provision of instrumental support) was more strongly associated with victimization and perpetration compared to previous day emotions. Strongest same-day positive associations were with partner’s perpetration, both partner’s jealousy, and females’ instrumental support. Partner’s jealousy and increased trust were best predictors of next day victimization. Closeness, commitment and trust went down on the day of violence. Perpetration was positively associated with next day commitment. Victimization was positively associated with next day trust. This event-level analysis demonstrates the role and timing that emotional aspects of adolescent relationships – including positive feelings – have surrounding episodes of dating violence. This granular understanding of the emotional context of dating violence has the potential to facilitate development of effective, developmentally appropriate interventions.